Prospects for peri-urban dairy development in Ethiopia - Tegegne, Azage; Gebre-Wold, A. (Ethiopian Society of Animal Production, 1998)
The human population in Ethiopia, currently estimated at 60 million is growing by about 3.5 percent per annum. This figure will increase to about 139 million by the year 2020, making Ethiopia the thrid most populous country in Africa. The number of children under the age of 15 is projected to increase from 26.7 million in 1994 to 59.0 million in 2020, and the number of women at peak childbearing age (20 to 35) is estimated to reach about 15 million by 2020 urbanization is projected to grow to 39.2 percent by 2000. As a result, the demand for animal products, both in terms of quantity and quality, is estimated to increase substantially. Currently, the population of cattle, sheep and goats is 30, 23 and 17 million, respectively, with an estimated annual milk production of 800,000. 65,000 and 95,000 metric tones, totalling to 960,000 metric tones. Over the period from 1975 to 1987 average annual milk consumption was estimated at 1,101,000 metric tones and per capita consumption was 25.6 kg/year. In 1995/96, the annual per capita consumption dropped to 17 kg. Comparative figures for other sub-Saharan African countries and the developed countries are 26 kg and 200 kg, respectively. Average milk production is estimated at 213 kg/cow/lactation. Almost all indigenous cattle are in the hands of the smallholder subsistence farmers and average milk production per cow per lactation is estimated at 213 kg. Milk produced is used for either family consumption or sold at local markets often processed into butter and ayib (cottage cheese). On the other hand, market-oriented dairy production systems with improved genotypes are found mainly in urban and peri-urban areas. The annual national demand-supply variance for fluid milk along, calculated on the basis of per capita consumption in sub-Saharan Africa, is estimated at 500 million kg. Based on this calculation, there will be a minimum annual demand for 1 billion 14 million kg of milk to satisfy the projected urban population of 39 million people by the year 2020. This is a great challenge and an opportunity for all people involved in the Development of the dairy sector. Currently, the emerging and fast growing peri-urban dairy production systems operating at different levels of intensification is becoming one of the most important and dominant systems, particularly around big urban centres. The expansion, further Development and sustainability of peri-urban dairy production systems has to be carefully examined as dairy production requires a relatively large initial investment and a long term commitment. In addition, the major technical and non-technical problems associated with these dairy production systems such as policy issues, land rights and ownership, availability and cost of dairy genotypes, feed resources and feeding systems, trained personnel, diseases, animal health and diseases, veterinary services, product quality, marketing, processing, absence of strong dairy association, etc. need to be addressed. In this paper, the status of dairy production in Ethiopia is assessed, and the potential for the Development of peri-urban dairy produciton systems and the major constraints associated are presented and discussed.